Biomass of Understorey Plants between 1.5 and 5.0m in a Logged-over Forest - Tsai, Lim Meng (1983)
The biomass of various comparzents of understorey plants ofa Lowland Dipterocarp Forest, between 1.5 and 5.0 m in height, was determined by harvesting 47 plants from a 0.01 ha plot. The total above ground biomass was equivalent to 2.78 tonnes/ha, and this was made up of 81 percent stem, 7.5 percent branch and 11.5 percent leaf The leaf area index (LAI) of the stratum was 0.36. Individual biomass of plant components and of the total plant was related to their collar girth. Using these regression equations, estimates based on measurements of collar girth in a 0.2 ha plot was found to be very close to that obtained by harvesting. This suggests that regression equations could be suitable for estimating biomass especially where no felling is allowed